Efficacy of insecticide mixtures against a resistant strain of house fly (Diptera: Muscidae) collected from a poultry farm. (16th January 2015) - Abbas, Naeem; Crickmore, Neil; Shad, Sarfraz Ali
Abstract : House flies ( Musca domestica L.) are key pests of poultry and are managed worldwide with a variety of insecticides. However, extensive and injudicious use of insecticides has led to the development of resistance in many insect pests. Insecticide mixtures can increase the efficacy of the product and/or delay the development of resistance, thus making them a useful tool for pest control. In addition to their efficacy when used alone, mixtures of emamectin benzoate, spinosad or nitenpyram with either lambda-cyhalothrin or profenofos were assessed against a susceptible strain of house flies collected from poultry farms. The analysis revealed that combination indices for lambda-cyhalothrin/emamectin benzoate and lambda-cyhalothrin/spinosad mixtures were significantly >1, indicating an antagonistic effect. In contrast, the indices for all the tested ratios of lambda-cyhalothrin/nitenpyram were significantly < 1, suggesting a synergistic effect. For mixtures containing profenofos, combination indices varied significantly. For example, synergism was observed in a 1:1 mixture containing lambda-cyhalothrin and emamectin benzoate, but antagonism occurred when a higher proportion of the latter insecticide was used. Conversely, synergism in a mixture containing profenofos and nitenpyram was observed only when a lower proportion of the second insecticide was used. The present results suggest that ideal insecticide mixtures must be empirically determined and alternative strategies such as mosaics, rotations and cultural control should be considered for the management of the house fly.